Associations of SARS-CoV-2 Vaccination During Pregnancy With Pregnancy Outcomes. Issue 1 (22nd March 2023) - Magnus, M.C.; Örtqvist, A.K.; Dahlqwist, E.; Ljung, R.; Skår, F.; Oakley, L.; Macsali, F.; Björn, P.; Gjessing, H.K.; Håberg, S.E.; Stephansson, O.
Abstract : ( JAMA . 2022;327:1469–1477) While pregnant patients are at a higher risk of severe COVID-19 infection, many may still be concerned about the safety of receiving the vaccines during pregnancy. There is evidence supporting the safety of the approved vaccines from the surveillance systems by the Center for Disease Control and Prevention, a few small studies, and data from unplanned pregnancies in the phase 3 vaccination trials. This study used data from Sweden and Norway to examine risk of adverse outcomes following COVID vaccination during pregnancy.